Original articleInfluence of serum and albumin on the in vitro anandamide cytotoxicity toward C6 glioma cells assessed by the MTT cell viability assay: implications for the methodology of the MTT tests - Bilmin, Krzysztof; Kopczyńska, Beata; Grieb, Paweł (Folia Neuropathologica, 2013)
Anandamide (AEA), an endogenous ligand of cannabinoid CB1 and CB2 receptors, which also binds transient receptor potential vanilloid type 1 receptor (TRPV1), has been shown to display substantial selective cytotoxicity toward some cancer cell lines in vitro , although the relevant data are not consistent. In the present study, we employed the MTT test to assess short-term cytotoxicity of AEA on C6 rat glioma cell culture. When anandamide was administered to the culture medium with foetal bovine serum (FBS), no cytotoxic effect was observed following 24 h exposure of the glioma cells to micromolar concentrations of AEA. However, if no serum was present in the medium, micro-to-submicromolar concentrations of AEA induced dose-dependent cytotoxicity clearly detectable after 24 h. Control experiments made it possible to exclude significant interference of serum with the MTT test per se. Bovine serum albumin mimicked the effect of FBS. We conclude that the apparent inhibition of short-term cytotoxicity of AEA toward C6 rat glioma cells in vitro is caused by binding AEA to serum proteins such as albumin. Taking into account that blood serum or albumin is practically always present in cell culture media, we discuss implications of binding substances to serum proteins for methodology and interpretation of in vitro cytotoxicity testing.